The Doctrine of Unlawful Acts in E-Commerce Consumer Protection - Pendang, Serlita Ruben (Journal of Law and Economics, 2025)
The development of digital technology has driven an increase in transactions through e-commerce platforms. However, this dynamic has also given rise to various violations of consumer rights, such as fraud, goods not as described, and misuse of personal data. This study aims to analyze the application of the doctrine of unlawful acts (PMH) in resolving disputes regarding consumer rights violations on e-commerce platforms. The method used is normative legal research with a statutory, conceptual, and case-based approach. The results show that the elements of PMH as stipulated in Article 1365 of the Civil Code can be applied to cases of consumer rights violations, whether committed by business actors or third parties. Furthermore, developments in jurisprudence have broadened the definition of PMH, allowing consumers to claim compensation not only when there is a violation of the law, but also when business actors act contrary to the principles of propriety, morality, and good faith. Thus, the PMH doctrine can be an important instrument in consumer protection in the digital era, although more stringent specific regulations regarding e-commerce are still needed.